Integration Of SPBE-Based Public Services In The Licensing Sector Of The Perkimta Office Of South Tangerang City - Sumawijaya, Hendri; Sartika, Ika (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study aims to analyze the implementation of the Electronic-Based Government System (SPBE) in the integration of public services, particularly in the licensing sector at the Housing, Settlement, and Land Agency (Perkimta) of South Tangerang City, as well as to identify the main supporting and inhibiting factors. Methodology/approach: This study uses a qualitative descriptive approach, utilizing in-depth interviews with Perkimta officials, direct observation of service processes, and analysis of relevant policy documents. Results/findings: Findings show that the implementation of SPBE has successfully integrated various licensing services into an integrated digital platform, significantly accelerating the process of permit application, verification, and issuance. The results of the study show that integrated licensing services greatly assist the administrative processes of the South Tangerang government. Conclusions: The study concludes that SPBE implementation in the Perkimta licensing sector enhances efficiency, transparency, and accountability in public services. Integrated digital systems simplify procedures and improve public trust, though sustained success depends on human resources readiness, infrastructure, and digital literacy. Limitations: This study focuses specifically on Perkimta licensing services in South Tangerang City, and these findings may not be fully applicable to other government agencies or regions with different levels of digital readiness. The time frame of the study also limits the assessment of long-term sustainability impacts. Contribution: This study provides valuable insights for policymakers and government agencies implementing digital transformation initiatives. It highlights the importance of simultaneous investment in technology infrastructure, human resource capacity building, and public digital literacy programs. The study also offers practical recommendations for improving system interoperability and data security in e-government services.